(6y - 11)(6y + 11) = ay
² - b |use (a - b)(a + b) = a² - b²
(6y)² - 11² =ay² - b
36y² - 121 = ay² - b |add b to both sides
ay² = 36y² - 121 + b |divide both sides by y² ≠ 0
a = (36y² - 121 + b)/y²
Answer: That would be a massive 1500% increase from 16 to 240
0 X 13 = 0
1 X 13 = 13
2 X 13 = 26
3 X 13 = 39
4 X 13 = 52
5 X 13 = 65
6 X 13 = 78
7 X 13 = 91
8 X 13 = 104
9 X 13 = 117
10 X 13 = 130
11 X 13 = 143
12 X 13 = 156
13 X 13 = 169
14 X 13 = 182
15 X 13 = 195
16 X 13 = 208
17 X 13 = 221
18 X 13 = 234
19 X 13 = 247
<span>20 X 13 = 260</span>
Answer:
2/3 > x
Step-by-step explanation:
0.5 > 0.75x
2/3 > x
Idk i can't see that, sorry